An Unmanaged World: A Philosophical Study of Global Dynamics - Chumakov, Alexander N., (Contemporary Russian Philosophy ;, 2026)
This book is devoted to the philosophical analysis of key problems of world development and prospects for global management. Based on both rich factual material and a holistic understanding of the world, the author shows how modern globalization has shifted the arena of interaction from individual territories and regions to the entire space of the Earth. The global problems resulting from this shift have led to a weakly regulated and unmanaged world, one that gives rise to acute contradictions for the world community. How can we improve this situation? According to the author, we must learn to "think globally and act together." This study argues that humanity needs a global civilizational revolution aimed at forming a planetary civil society and initiating a shift within international relations, from the "right of power" to the "power of law."